Indicators of the Functional State of Adolescents with Impaired Vision - Norqobilov Mukhiddin Najimovich (Scientific Trends, 2025)
The article assesses the functional state of adolescents with visual impairments. In visually impaired adolescents, respiratory system indicators, Rufier-Dixon indicators characterizing physical performance, the Yarotsky test assessing the ability to maintain balance are also characterized by below-average values.
Keywords: Respiratory system, Yarotsky test, vestibular analyzer, physical performance, visually impaired adolescents, functional training, dynamometry.